The Impact Transfer of Power In Afghanistan From President Ashraf Ghani To The Taliban In South Asia Regional Security 2021 (International Journal of Scientific Research and Management (IJSRM), 2024)
The international world is very shocked by the handover of power in Afghanistan that does not require military force carried out by a movement known as the Taliban. This study aims to determine the Taliban movement that is able to dominate Afghanistan and see its impact both on a national and regional scale in South Asia. The theory used is Transfer of Power and Regional Security. The method used in this paper is qualitative, namely explaining the phenomenon in depth by collecting data continuously. The implementation of this research procedure is by interviewing, observing and using data sourced from documents.